2001
DOI: 10.1086/317902
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Analysis of the Breeding System and Seed Dispersal in Shorea leprosula (Dipterocarpaceae)

Abstract: To understand the breeding system and seed dispersal in Shorea leprosula (Dipterocarpaceae) in Peninsular Malaysia, a microsatellite analysis was conducted of embryos of immature and mature fruits fallen in litter traps under the crowns of five trees. Outcrossed and selfed progeny mothered by the trees and those dispersed from other trees were distinguished by genotypes of three polymorphic microsatellite loci. The mean outcrossing rate of mature fruit embryos in S. leprosula pollinated by thrips (0.91) was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 14 publications
(23 reference statements)
2
29
1
1
Order By: Relevance
“…On the other hand, some insights about the effective population size could be gleaned from the ecological characteristics of Shorea species. First, Shorea species are predominantly outcrossing and they are partially self-incompatible (Chan, 1981;Nagamitsu et al, 2001;Obayashi et al, 2002;Sakai et al, 1999). However, their pollinators are mainly thrips and beetles, which can migrate only limited distance (Appanah & Chan, 1981;Sakai et al, 1999).…”
Section: Low Levels Of Dna Polymorphism Within Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some insights about the effective population size could be gleaned from the ecological characteristics of Shorea species. First, Shorea species are predominantly outcrossing and they are partially self-incompatible (Chan, 1981;Nagamitsu et al, 2001;Obayashi et al, 2002;Sakai et al, 1999). However, their pollinators are mainly thrips and beetles, which can migrate only limited distance (Appanah & Chan, 1981;Sakai et al, 1999).…”
Section: Low Levels Of Dna Polymorphism Within Speciesmentioning
confidence: 99%
“…Lee et al (2000) showed high heterozygosity in Shorea leprosula using allozyme markers. Shorea curtisii and S. leprosula were studied using microsatellites showing high (>90%) outcrossing rate (Lee et al, 2000;Nagamitsu et al, 2001;Obayashi et al, 2002). Harada et al (1994) investigated S. acuminata, S. curtisii and S. leprosula using RAPD markers and found low inter-specific nucleotide divergence and high within species diversity, suggesting that the diversification of the genus Shorea occurred only recently and/or that there is considerable gene exchange among species.…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit high outcrossing rates associated with close to complete self-incompatibility (Loveless, 1992;Doligez and Joly, 1997;Nason and Hamrick, 1997). Nevertheless, in pristine or 'little disturbed' habitats pollination often occurs preferentially between neighboring conspecifics resulting in correlated matings (Murawski and Hamrick, 1991;Stacy et al, 1996;Dawson et al, 1997;Kaufman et al, 1998;Nagamitsu et al, 2001;Dutech et al, 2002) though often in association with substantial long-distance pollen dispersal (Hamrick and Murawski, 1990;White et al, 2002;Latouche-Hallé et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The reported heterozygosities of these loci in Shorea critesii were 0.591, 0.844 and 0.640, respectively (Ujino et al, 1998). Nagamatsu et al (2001) reported values of 0.568, 0.795 and 0.614 in Shorea leprosula in Pasoh Forest Reserve for the loci Shc03, Shc07 and Shc09, respectively. The heterozygosities observed in our study are similar to the values in these studies.…”
Section: Mating System In the Natural Forestmentioning
confidence: 93%
“…Significant departure from HWE was observed in D. lancelolata and S. macrophylla. The mating system of some tropical tree species has been investigated using isozymes (Murawski & Hamrick, 1991;Bawa, 1992;O'Malley & Bawa, 1987;Kitamura et al, 1994) and microsatellites (Nagamatsu et al, 2001). Shiraishi et al (1990) studied the mating system of D. aromatica using isozymes in the Andulau Forest Reserve in Brunei and found that surviving seedlings were the products of random mating.…”
Section: Mating System In the Natural Forestmentioning
confidence: 99%